Local Landscapes and Constructions of World Space: Medieval Inscriptions, Cognitive Dissonance, and the Course of the Niger - Paulo Fernando de Moraes Farias (Afriques)
In the West African Sahel, Islam induced processes of cognitive change as spaces and history were given new meaning over time. In the expanding Muslim universe, they were reconstructed with reference to the core regions of the Islamic world and the founding events of Islam. This brought issues of cognitive dissonance to the interpretation of the past, when people were simultaneously confronted with different and incompatible heuristic heritages. This paper investigates such changes in the representation of the past in the Tadmăkkăt / Ǝssuk valley of northern Mali between the Middle Ages and the 1980s. As social interactions were restructured and renegotiated among nomads from the seventeenth century onwards, some groups formulated new status claims by borrowing afresh from the Islamic repertoire. The commercial role the area had played in the Middle Ages ceased to be worth remembering. A new interpretation of the past was imposed upon the valley, and even well-dated Arabic medieval inscriptions were given new meaning. After 1980, the rise of Tuāreg nationalism fostered yet another interpretation of the past of the ancient site. Cognitive dissonance is also displayed in the descriptions of the course of the Niger provided by Leo Africanus in the 16th century, and Muḥammad Bello in the 19th.